2011
DOI: 10.2337/dc10-2222
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Peripheral Neuropathy Is Associated With Increased Arterial Stiffness Without Changes in Carotid Intima–Media Thickness in Type 2 Diabetes

Abstract: OBJECTIVEThis study was conducted to investigate the association of diabetic peripheral neuropathy (DPN) with both arterial stiffness and intima–media thickness (IMT).RESEARCH DESIGN AND METHODSWe conducted a cross-sectional analysis of 731 subjects with type 2 diabetes. DPN was diagnosed on the basis of neuropathic symptoms, insensitivity to a 10-g monofilament, abnormal pin-prick sensation, and abnormal current perception threshold. Arterial stiffness was assessed by cardio-ankle vascular index (CAVI), and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 14 publications
4
50
0
3
Order By: Relevance
“…Patients with type 2 diabetes have also demonstrated higher CAVI scores when they also present with diabetic peripheral neuropathy, 36 microvascular conditions, 14 intima-media Data presented as mean AE SD or n (%) of patients. a P < 0.05; continuous variables between the two groups were compared using an unpaired Student's t-test; categorical variables were compared between the two groups using 2 -test.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 2 diabetes have also demonstrated higher CAVI scores when they also present with diabetic peripheral neuropathy, 36 microvascular conditions, 14 intima-media Data presented as mean AE SD or n (%) of patients. a P < 0.05; continuous variables between the two groups were compared using an unpaired Student's t-test; categorical variables were compared between the two groups using 2 -test.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 39) reported that diabetic peripheral neuropathy was associated with increased CAVI without changes in carotid IMT in type 2 diabetes. Kim et al 40) found that increased CAVI in type 2 diabetes was associated with the presence of arterial plaque, increased IMT, and microvascular complication.…”
Section: (B) Diabetes Mellitusmentioning
confidence: 99%
“…3 Studies suggest that at the time of diagnosis, the typical patient with type 2 diabetes mellitus have diabetes for at least 4 to 7 years. 4 Among patients with type 2 diabetes mellitus, 25% are believed to have retinopathy, 9% nephropathy and 8% neuropathy at the time of diagnosis. 5 Daruka et al has also reported that in addition to hyperosmolar coma and ketoacidosis, patients with type 2 diabetes may have cardiovascular disease, nephropathy, retinopathy and polyneuropathy.…”
Section: Introductionmentioning
confidence: 99%